Edukasi dan Partisipasi Masyarakat dalam Pelestarian Ekosistem Pesisir di Kampung Melayu, Kota Batam - Imam Arief; Julita Dewi; Reva Amalia; Nurul Adilah; Aisyah Faras; Rosita Septiani (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Abstract. Coastal ecosystem sustainability is closely related to the knowledge, awareness, and participation of local communities. Environmental education is an approach that can improve public understanding of coastal ecosystems and encourage participation in conservation activities. This community service activity aimed to increase community knowledge and participation in supporting coastal ecosystem conservation in Kampung Melayu, Batam City. The activity used a descriptive approach supported by pre-test and post-test evaluations, observation, interviews, and documentation. The educational activity involved 15 participants and covered coastal ecosystems, mangrove benefits, waste impacts, waste management, and community roles in coastal conservation. The results showed that participants' knowledge increased from 60% before the activity to 85% after the activity, representing an increase of 25 percentage points. Community participation was demonstrated through direct involvement in conservation activities, including planting 50 mangrove seedlings and conducting environmental clean-up activities. The results indicate that environmental education can increase community knowledge and provide a foundation for participatory conservation actions. Program sustainability requires continuous education, routine monitoring, mangrove maintenance, waste management, and collaboration among communities, universities, government, and other stakeholders.